2020
DOI: 10.21037/jtd-20-1280
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between quantitative computed tomography, scintigraphy, and anatomical methods for prediction of postoperative FEV1 and DLCO: effects of chronic obstructive pulmonary disease status and resected lobes

Abstract: Background: Postoperative assessment of pulmonary function is important for estimating the risk of thoracic surgery and long-term disability following pulmonary resection, including predicted postoperative (ppo) forced expiratory volume (FEV) in one second (ppoFEV 1 ) and percent predicted lung diffusion capacity for carbon monoxide (ppo%DLCO) estimation. The ppo values were compared using four different estimation methods between chronic obstructive pulmonary disease (COPD) and non-COPD patients and according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Similar results was demonstrated by Sverzellati et al, who reported a significant correlation between estimated FEV1 and measured FEV1 values (r = 0.97) three months after surgery [ 9 ]. According with our findings, Yokoba et al identified a significant correlation between postoperative FEV1 and %DLCO and corresponding predicted values obtained by QCT; nevertheless, our results showed a higher tendency to underestimate PFTs, likely for the narrower range of CT density considered as WAL in our study (between −950 and −750 HU vs. −950 and −600 HU) [ 8 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results was demonstrated by Sverzellati et al, who reported a significant correlation between estimated FEV1 and measured FEV1 values (r = 0.97) three months after surgery [ 9 ]. According with our findings, Yokoba et al identified a significant correlation between postoperative FEV1 and %DLCO and corresponding predicted values obtained by QCT; nevertheless, our results showed a higher tendency to underestimate PFTs, likely for the narrower range of CT density considered as WAL in our study (between −950 and −750 HU vs. −950 and −600 HU) [ 8 ].…”
Section: Discussionsupporting
confidence: 80%
“…Emerging techniques, such as CT ventilation imaging, strongly correlate with PET ventilation in evaluating relative lobar function; nevertheless, it requires images acquired at end-expiration and end-inhalation, increasing radiation exposure [ 7 ]. QCT has the potential to predict post-surgical lung function by quantifying the ventilated area of the lobe that might be resected [ 8 , 9 ]. Several types of software can calculate, on the basis of CT Hounsfield units (HU) thresholds, the well-aerated lung (WAL) as a surrogate of normal lung [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who had poor lung function were excluded during the study design. Therefore, quantitative ventilation-perfusion scans would be not essential in this study (32)(33)(34), and the results could not be extrapolated to patients with poor lung function. Then segmental planes were divided by staplers in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Brunelli et al reported similar results regarding extended lung resection, suggesting that measurements of ppoFEV1 for pneumectomies need to be reconsidered [ 13 , 14 , 22 ]. Brunelli et al showed similar results for extended lung resection, even stating, that measurements of ppoFEV1 for risk stratification for pneumectomies need to be reconsidered [ 9 , 13 ]. Therefore, we excluded pneumectomy patients for our customized FEV1 (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Yokoba et al found that COPD is an independent factor for an inaccurate ppoFEV1. The authors suggest separating the calculation of patients with and without COPD [ 13 ].…”
Section: Discussionmentioning
confidence: 99%